PENGARUH PROMOSI JABATAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN NON-MEDIS PADA RS SYAFIRA PEKANBARU - Maya Kharisma; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at Syafira Pekanbaru Hospital with the problem of this research is low employee performance. The purpose of this research is to know and analyze the influence of promotion position and working discipline on partial and simultaneous employee performance. This research uses questionnaires as a data collection tool distributed to 75 respondents to non-medical employees of the Pekanbaru Syafira Hospital. Further Data is processed with descriptive analysis and quantitative analysis by using SPSS by conducting validity tests, reliability tests, simple linear regression analyses, multiple linear regression analyses, analysis of determinations (R2), and hypothesis tests with T (partial) tests and F (simultaneous) tests.  The results of this study showed that the first hypothesis test is the promotion of the position to the employee's performance, that is thitung (8,376) >ttabel (1,99300), which means the promotion of the position of significant impact on employee performance. Secondly, the working performance of the employees thitung (8,850) >ttabel (1,99300) means that the working discipline has significant effect on the employee's performance. Test result Fhitung (77,839) > Ftabel (3,12), which means that the promotion of job titles and discipline simultaneously has a significant impact on employee performance.  Key Words :Job Promotion, Work Dicipline, Empolyee Performance